Political Communication by Members of the Mojokerto City Regional People's Representative Council In Maintaining Public Accountability - Budiarto Budiarto; Suprihatin Suprihatin (Prodi Ilmu Komunikasi UTM, 2026)
This study analyzes the political communication styles of members of the Mojokerto City Regional Representative Council (DPRD) and their implications for enhancing public accountability. In an era of information openness and increasing demands for transparency, political communication plays a crucial role in strengthening public trust in legislative institutions. This study employs a qualitative descriptive approach using in-depth interviews and observation. Informants included members of the Mojokerto City DPRD. Findings indicate that political communication styles span a spectrum ranging from dialogic-participatory approaches to formal and closed ones. Open and responsive communication styles positively influence public perceptions of accountability, while one-way communication tends to erode public trust. This study recommends strengthening political communication capacity and optimizing the use of digital media. A key contribution of this research lies in advancing understanding of the relationship between local legislators’ political communication styles and public accountability practices at the local level. Furthermore, this study offers a conceptual model suggesting that participatory and transparent political communication can serve as a strategic instrument in strengthening political legitimacy, enhancing citizen engagement, and fostering more accountable and democratic local governanc